A bio-instructive, bioactive in situ polymerizable wound matrix promotes scar-free burn wound repair - Ayesha Aijaz; Margarita Elloso; Yufei Chen; Faraz Chogan; Bhavishya Challagundla; Graham Rix; Supriya Hota; Anna Matveev; Marc G. Jeschke (iScience)
Summary: Early initiation of wound regeneration and healing is the primary determinant of survival for burn patients. While superficial burns do not require secondary interventions and undergo spontaneous healing, full-thickness burns exceed the intrinsic capacity of body to induce skin regeneration. Herein, we developed a wound matrix system, referred to as PEGScarX that provides critical bioactive and bio-instructive cues to modulate cell fate decisions for burn wound healing. Our results indicate that PEGScarX promotes faster wound healing kinetics and reduces scar formation in burn wounds. PEGScarX induces fibroblast and epidermal stem cell repopulation, inhibits transdifferentiation of fibroblasts to myofibroblasts, and induces a pro-regenerative immune cell niche. These findings unravel an opportunity to reduce morbidity and mortality in burn patients due to inadequate wound regeneration and reduce the occurrence of pathological scaring.